Atypical attentional filtering of visual information in youth with chromosome 22q11.2 deletion syndrome as indexed by event-related potentials - S.R. Linton (Elsevier, 2021)
Background: Youth with chromosome 22q11.2 deletion syndrome (22q) face one of the highest genetic risk factors for the development of schizophrenia. Previous research suggests impairments in attentional control and potential interactions with elevated anxiety and reduced adaptive functioning may increase the risk for developing psychosis in this population. Here, we examined how variations in attentional control relate to the presence or severity of psychosis-proneness symptoms in these individuals. Methods: To achieve this, we measured attentional control in youth (12–18 years) with 22q (N = 35) compared to a typically developing group (N = 45), using a flanker task (the Distractor Target task) while measuring neural activity with event-related potentials. Results: Similar to previous findings observed in people with schizophrenia, greater attentional capture by, and reduced suppression of, non-target flanker stimuli characterized participants with 22q and was indexed by the N2pc (N2-posterior-contralateral) and PD (distractor positivity) components. Although we observed no relationships between these components and measures of psychosis-proneness in youth with 22q, these individuals endorsed a relatively low incidence of positive symptoms overall. Conclusions: Our results provide neural evidence of an attentional control impairment in youth with 22q that suggests these individuals experience sustained attentional focus on irrelevant information and reduced suppression of distracting stimuli in their environment. Impairments in attentional control might be a valid biomarker of the potential to develop attenuated positive symptoms or frank psychosis in high-risk individuals long before the age at which such symptoms typically arise. The evaluation of such a hypothesis, and the preventive potential for the putative biomarker, should be the focus of future studies.